Sexual dimorphic responses in lymphocytes of healthy individuals after Carica papaya consumption - Jumat, Nur Ramziahrazanah; Mun, Yee Chong; Seman, Zainina; Jamaluddin, Rosita; Nyet, Kui Wong; Abdullah, Maha (Frontiers Research Foundation, 2017)
Sexual dimorphism in immune response is widely recognized, but few human studies have observed this distinction. Food with endo-immunomodulatory potential may reveal novel sex-biased in vivo interactions. Immunomodulatory effects of Carica papaya were compared between healthy male and female individuals. Volunteers were given fixed meals supplemented with papaya for 2 days. Changes in blood immune profiles and hormone levels were determined. In females, total natural killer (NK) cell percentages decreased (12.7 ± 4.4 vs 14.6 ± 5.8%, p = 0.018, n = 18) while B cells increased (15.2 ± 5.5 vs 14.5 ± 5.0, p = 0.037, n = 18) after papaya consumption. Increased 17β-estradiol (511.1 ± 579.7 vs 282.7 ± 165.0 pmol/l, p = 0.036, n = 9) observed in females may be crucial to this change. Differentiation markers (CD45RA, CD69, CD25) analyzed on lymphocytes showed naïve (CD45RA+) non-CD4+ lymphocytes were reduced in females (40.7 ± 8.1 vs 46.8 ± 5.4%, p = 0.012, n = 8) but not males. A general suppressive effect of papaya on CD69+ cells, and higher percentage of CD69+ populations in females and non-CD4 lymphocytes, may be relevant. CD107a+ NK cells were significantly increased in males (16.8 ± 7.0 vs 14.7 ± 4.8, p = 0.038, n = 9) but not females. Effect in females may be disrupted by the action of progesterone, which was significantly correlated with this population (R = 0.771, p = 0.025, n = 8) after papaya consumption. In males, total T helper cells were increased (33.4 ± 6.4 vs 32.4 ± 6.1%, p = 0.040, n = 15). Strong significant negative correlation between testosterone and CD25+CD4+ lymphocytes, may play a role in the lower total CD4+ T cells reported in males. Thus, dissimilar immune profiles were elicited in the sexes after papaya consumption and may have sex hormone influence.